Pengaruh Gender Dan Manifestasi Kardiovaskular Pada COVID-19 - Dyana Sarvasti (The Indonesian Heart Association, 2020)
Cardiovascular manifestations, in the form of myocardial injury, can occur in patients infected with COVID-19. Data collected from various COVID-19 pandemic case reports indicated that male patients experience myocardial injury more frequently than females. However, not any definitive mechanism has been found yet that underlies susceptibility to myocardial injury due to infection with SARS-CoV-2 attributable to gender differences. Some theories propose are differences in the number of X chromosomes, the influence of sex hormones, and differences in immune reactions between males and females. A further comprehensive research needs to be done on the mechanism of cardiovascular manifestations and the effect of gender on COVID-19 disease. Keywords: Gender, cardiovascular manifestation, myocardial injury, COVID-19.